2020
DOI: 10.24815/jimeka.v5i2.15559
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pemanfaatan Sistem Informasi Akuntansi Keuangan Daerah, Kualitas Sumber Daya Manusia, Dan Pengawasan Keuangan Daerah Terhadap Kualitas Laporan Keuangan Pemerintah Aceh

Abstract: The research examines the influence of the use of regional financial accounting information system, quality of human resources and regional financial supervision on the quality of  the Aceh Goverment financial report. The population in this study is SKPA of Aceh Province. The sampling technique used is simple random sampling. This study uses primary data which obtained through the questionnaire results. The data were colleccted 64 questionnaires from 32 SKPA. Data analysis using multiple linear regression. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
1
0
3
Order By: Relevance
“…This pattern manifests in the form of regional self-reliance and high accountability in the financial reporting of local governments. Muraiya and Nadirsyah (2018), as well as Mudhofar and Afrizal Tahar (2016), have also found that budget prediction has a positive impact on the accountability of financial reporting in local governments in Indonesia. This research contributes to the pace of economic growth in districts and cities in the South Sulawesi Province.…”
Section: Figurementioning
confidence: 88%
“…This pattern manifests in the form of regional self-reliance and high accountability in the financial reporting of local governments. Muraiya and Nadirsyah (2018), as well as Mudhofar and Afrizal Tahar (2016), have also found that budget prediction has a positive impact on the accountability of financial reporting in local governments in Indonesia. This research contributes to the pace of economic growth in districts and cities in the South Sulawesi Province.…”
Section: Figurementioning
confidence: 88%
“…Sistem informasi akuntansi pada pemerintah daerah juga lebih dikenal dengan nama sistem informasi keuangan daerah (SIKD), yaitu suatu sistem yang mendokumentasikan, mengadministrasikan serta mengolah laporan keuangan daerah dan data terkait lainnya menjadi informasi yang disajikan kepada masyarakat sebagai bahan pengambilan keputusan dalam rangka perencanaan, pelaksanaan, dan pelaporan pertanggungjawaban pemerintah daerah. Sedangkan suatu informasi keuangan daerah adalah segala informasi yang berkaitan dengan keuangan daerah yang diperlukan dalam rangka penyelenggaraan sistem informasi keuangan daerah (Rosmalita & Nadirsyah, 2020).…”
Section: Pemahaman Akuntansiunclassified
“…Kerangka Penelitian Hasil penelitian Kesuma, dkk (2018) bahwa kompetensi aparatur pemerintah memiliki pengaruh signifikan terhadap kualitas laporan keuangan pemerintah di satuan kerja Kementerian Pariwisata. Penelitian ini di dukung oleh penelitian (Naholo 2021; Sikumbang, dkk., 2021;Hidayat, dkk., 2021;Sukarman dan Solovida, 2021;Rosmalita dan Nadirsyah, 2020;Laitera, dkk., 2021;Darwin dkk., 2020). Sementara hasil penletian (Zalni 2021 dan Safitri, dkk., 2021) menunjukan hasil yang berbeda yaitu kompetensi aparatur pemerintah tidak berpengaruh terhadap kualitas laporan keuangan pemerintah daerah.…”
Section: Kerangka Penelitianunclassified